Correlation of microRNA-146a/b with disease risk, biochemical indices, inflammatory cytokines, overall disease severity, and prognosis of sepsis. Issue 22 (29th May 2020) - Chen, Li; Yu, Lili; Zhang, Rixin; Zhu, Ling; Shen, Wanqi
Abstract: Background: Previous studies have indicated the association of microRNA-146a/b (miR-146a/miR-146b) with pro-inflammatory cytokines production, lipopolysaccharide-mediated injuries and organ dysfunction, however, the correlation of miR-146a/miR-146b with disease risk, disease severity, biochemical indices, inflammatory cytokines and mortality of sepsis has not been explored, which was investigated in the present study. Methods: In total, 180 sepsis patients and 180 healthy controls were enrolled. The peripheral blood samples were collected from sepsis patients within 24 hour after admission and from healthy controls at enrolment. Furthermore, MiR-146a/miR-146b expressions in plasma were detected by reverse transcription quantitative polymerase chain reaction. Results: MiR-146a and miR-146b expressions were higher in sepsis patients compared to healthy controls. MiR-146a (AUC: 0.774, 95%CI: 0.727–0.820) and miR-146b (AUC: 0.897, 95%CI: 0.865–0.929) were both of good value in predicting increased sepsis risk, among which miR-146b presented a superior predictive value. In sepsis patients, MiR-146a expression was positively associated with miR-146b expression. Besides, MiR-146a and miR-146b expressions were positively correlated with acute pathologic and chronic health evaluation II score, sequential organ failure assessment score, serum creatinine, C-reactive protein, tumor necrosis factor-α, interleukin (IL)-1β, IL-6, IL-17, while negatively correlated with albumin. Based on the survival status in 28-day follow-up, MiR-146a and miR-146b expression were both increased in survivors compared to deaths. miR-146b presented relatively good predictive for increased 28-day mortality risk (AUC: 0.703, 95%CI: 0.617–0.788), but MiR-146a was of poor value in predicting increased 28-day mortality risk (AUC: 0.599, 95%CI: 0.511–0.688). Conclusion: MiR-146b presents superior potential as a prognostic biomarker in sepsis patients compared to MiR-146a, which implies the clinical application of miR-146b in disease management of sepsis. Abstract : Supplemental Digital Content is available in the text